The effect of geometry on tumor thermal profile and its use in tumor functional state estimation. Issue 3 (26th March 2014) - Tepper, Michal; Shoval, Asaf; Gannot, Israel
Abstract : Thermal differences between transplanted tumors and tumors in humans prevent the implementation of thermographic methods developed in mice models to human models and vise‐versa. Transplantable tumors tend to have an extruding shape, which may affect the thermal patterns. This hypothesis was studied in phantom experiments and simulations. A correlation between tumor dimensions and relative temperature was found and used to estimate tumor functional state from previously published in vivo experiments. A correlation was found between temperature differences and tumor growth rates (tumor aggressiveness) and the effect of tumor treatment was demonstrated, showing the potential for in vivo, non‐invasive tumor monitoring. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : Thermal differences between transplanted tumors and tumors in humans prevent implementation of thermographic methods between animal and human models. Phantom experiments and simulations are used to show the cause is the extruding shape of the tumors. Formulating this correlation enables the estimation of tumor functional state in vivo. The calculated tumor temperature differences are correlated with tumor aggressiveness and treatment, showing the potential for in vivo, non‐invasive tumor monitoring.